Translating from Igbo (Nigeria) – A Bumpy Journey - Ugochukwu, Françoise (Global Journal of Cultural Studies, 2025)
Literatures in African languages have remained largely untranslated and thus unknown outside their linguistic domain. This situation led the ELLAF http://ellaf.huma-num.fr/ team to start gathering oral and written texts and build an online encyclopaedia of literatures in African languages. Igbo language, one of the three major national Nigerian languages, is also one of the eleven African languages chosen for this project. Igbo rich oral and written literature remains largely unknown to this day, with only one translation into French, that of its first novel, Omenuko (1933). This article will present the difficulties and challenges experienced by the French translation of the Igbo text during this long period, from a first attempt in the 1990s unto its 2010 publication in Paris. It will equally contribute to the on-going reflection on challenges facing the translation and publication of literary texts in African languages.